Evaluation of slopes failure base on SPT (N-values) And JKR probe tests in tropical residual soil in Northern Malaysia / Muhammad Hafeez Osman, Damanhuri Jamalludin and Mohamad Irwan Pandapotan Harahap - Osman, Muhammad Hafeez; Jamalludin, Damanhuri; Harahap, Mohamad Irwan Pandapotan (Institute of Research, Development and Commercialization, Universiti Teknologi MARA, 2012)
Slope failures are generally caused by infiltration due heavy and intense rainfall, very steep slope angle, erosion of slope surface and slope toe, vibration due to blasting, rise of water table in slope and etc. Slopes will be more stable when they are having gentler slope angle, proper drainage on the slope such as providing interceptor drain and berm drain, proper vegetations are planted on slope surface such as hydroseeding,turfmg and etc. The objectives of this research is to determine the relationship between allowable bearing capacity obtained from results of JKR Probe and physical soil characteristic obtained from particles size distribution curves. A total of 10 un-failed slope locations were selected in Northern Malaysia. Five un-failed slope locations were selected along Jalan Gertak Sanggul, Pulau Pinang and another five locations were selected in Baling District, Kedah. The un-failed slopes along Jalan Gertak Sanggul were situated near a village called Kampung Gertak Sanggul while the un-failed slope in Baling is road along Baling town to Grik, Perak. Six numbers of JKR Probe tests were conducted and four soil samples were collected at each un-failed slope location. Soil samples were collected at about 100mm below the existing ground level. It was found that the un-failed slope consists of silts, sandy, very silty sand and very silty gravel with silt has the widest range of numbers of blows / 300mm penetration compared to other soil types.